Sociodemographic Profile among the Victims of Road Traffic Accident Reported in a Tertiary Level Hospital: A Cross Sectional Observation - Rahman, Md Moshiur; Uddin, Abu Noman Md Mosleh (Anwer Khan Modern Medical College Journal, 2020)
Introduction: Road traffic accident is an unbaiting concern of health security issues to the community in Bangladesh. Every individual RTA contributes a tragic social impact due to its morbidity or mortality associated to each family. Objectives: To assess the sociodemographic profile among the victims of RTA. Material and Methods: This cross sectional study was conducted in 2010 among purposively selected 126 victims of road traffic accident reported to the medical inspection room of Combined Military Hospital Dhaka.Data were collected by a structured questionnaire through the review of medical records of the patients. Results: More than half (53.2%) of the respondents were in the age group of 21-40 years and 44.4% were educated up to SSC level. Majority of them (8 1 .7%) were Male and 45.23.8% were from military service. About 27.3% of RTA occurred by truck/covered van/Bus/ minibus which was followed by Jeep/car/microbus and pickup (35.7%) and 44.4% of the affected respondents were from motor vehicle passengers which was followed by pedestrian (37.3%). Majority ofthe patients experienced laceration and cut injuiy (38.1%) which was equally followed by abrasion and fracture (15.9%). Statistically significant (p<0.05) association revealed between education with role of affected personand occupation with morbidity pattern. Conclusion: As the victims of RTA are mainly male in active and productive period of life, so this group should be motivated. AKMMC J 2020; 11(2) : 102-106